A functional MRI study of altered spontaneous brain activity pattern in patients with congenital comitant strabismus using amplitude of low-frequency fluctuation - Tan G; Huang X; Zhang Y; Wu A; Zhong Y; Wu K; Zhou F; Shao Y (Neuropsychiatric Disease and Treatment)
Gang Tan,1,2,* Xin Huang,1,3,* Ying Zhang,1 An-Hua Wu,2 Yu-Lin Zhong,1 Kai Wu,2 Fu-Qing Zhou,4 Yi Shao1 1Department of Ophthalmology, The First Affiliated Hospital of Nanchang University, Jiangxi Province Clinical Ophthalmology Institute and Oculopathy Research Centre, Nanchang, Jiangxi, 2Department of Ophthalmology, The First Affiliated Hospital of University of South China, Hengyang, Hunan, 3Department of Ophthalmology, The First People’s Hospital of Jiujiang City, Jiujiang, 4Department of Radiology, The First Affiliated Hospital of Nanchang University, Jiangxi Province Medical Imaging Research Institute, Nanchang, Jiangxi, People’s Republic of China *These authors contributed equally to this work Objective: The aim of this study was to use amplitude of low-frequency fluctuation (ALFF) to investigate local features of spontaneous brain activity in patients with congenital comitant strabismus and clarify their relationship with emotional and psychosocial problems. Methods: A total of 20 patients with congenital comitant strabismus (ten males and ten females), and 20 healthy controls (ten males and ten females) closely matched in age, sex, and education underwent resting-state functional magnetic resonance imaging scans. The ALFF method was used to assess local features of spontaneous brain activity. Congenital comitant strabismus patients were distinguished from healthy controls by receiver operating characteristic curve. Correlation analysis was performed to explore the relationships between the observed mean ALFF signal values of the different areas and the Chinese version of the Hospital Anxiety and Depression Scale. Results: Compared with healthy controls, patients with congenital comitant strabismus had significantly lower ALFF in the bilateral medialfrontal gyrus and higher values in the bilateral cerebellum posterior lobe and left angular gyrus. In the congenital comitant strabismus group, the Hospital Anxiety and Depression Scale-depression score showed a negative correlation with the ALFF signal values of the bilateral medial frontal gyrus (r=-0.550, P=0.012) and a negative correlation was noted between the mean ALFF signal values of the left angular gyrus and strabismus duration (r=-0.515, P=0.020). Conclusion: Congenital comitant strabismus mainly involves dysfunction in the bilateral medial frontal gyrus, bilateral cerebellum posterior lobe, and left angular gyrus, which may reflect the underlying pathologic mechanism of congenital strabismus. Keywords: ALFF, congenital comitant strabismus, resting state, spontaneous activity, anxiety and depression